Pengendalian Wildlife Hazard oleh Unit Safety Risk & Quality Control di Area Airside Bandar Udara Internasional H.A.S. Hanandjoeddin Tanjung Pandan - Fitri Budiarti (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The importance of the role of the Safety Risk &; Quality Control unit at H.A.S. Hanandjoeddin Tanjung Pandan International Airport, makes the Executive General Manager must implement safety in the Safety Risk &; Quality Control unit assigned to handle wildlife hazard with standards that must be met to ensure flight safety can be managed properly because aviation accidents can cause many material losses, financial and fatalities. This study aims to find out how the Safety Risk &; Quality Control Unit controls the Wildlife Hazard and to find out how the Safety Risk &; Quality Control unit coordinates with other units in handling Wildlife Hazard at the airside of H.A.S. Hanandjoeddin Tanjung Pandan International Airport. This study used qualitative research methods using three data collection techniques in the form of observation, interviews and documentation. The interview used a semi structured technique and five sources as information. To analyze the data that has been collected using three techniques, namely data reduction, data display and Conclusion drawing / verification. The results showed that in order to wildlife hazard control at the International airport H.A.S. hanandjoeddin tanjun pandan, the safety & quality control unit conducted the three-way prepararation of toxins, wedges and shootings. If there is a report about the presence of wild animals the SRQC unit will coordinate with the AMC, ATC, AVSEC, PKP-PK units and the Maintenance Unit for handling wildlife hazard. This action is in the form of expulsion using vehicles and the provision of poison and shooting to reduce the population of wild animals passing through the airport area.